2016 28th International Teletraffic Congress (ITC 28) 2016
DOI: 10.1109/itc-28.2016.148
|View full text |Cite
|
Sign up to set email alerts
|

ModelGraft: Accurate, Scalable, and Flexible Performance Evaluation of General Cache Networks

Abstract: Large scale deployments of general cache networks, such as Content Delivery Networks or Information Centric Networking architectures, arise new challenges regarding their performance evaluation for network planning. On the one hand, analytical models can hardly represent in details all the interactions of complex replacement, replication, and routing policies on arbitrary topologies. On the other hand, the sheer size of networks and content catalogs makes event-driven simulation techniques inherently non-scala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The proposed News Feed model relies on TTL counters. TTL-based caching mechanisms are versatile and flexible, and can be used to reproduce the behavior of traditional caching policies such as LRU and FIFO [37,81,21,36,64]. In this paper, we leverage the analytical tractability of TTL-based caches, showing how to adapt them for the purposes of modeling and optimization of the News Feed.…”
Section: Social Network Ttl-counters and Utility-based Allocationmentioning
confidence: 99%
“…The proposed News Feed model relies on TTL counters. TTL-based caching mechanisms are versatile and flexible, and can be used to reproduce the behavior of traditional caching policies such as LRU and FIFO [37,81,21,36,64]. In this paper, we leverage the analytical tractability of TTL-based caches, showing how to adapt them for the purposes of modeling and optimization of the News Feed.…”
Section: Social Network Ttl-counters and Utility-based Allocationmentioning
confidence: 99%
“…As a consequence, the pivotal role of inversion rejection sampling in studying cache dynamics at Internet-scale (i.e., with trillion objects [33]) becomes clear. Formally (proof available in [45]):…”
Section: Methodsmentioning
confidence: 99%
“…where W is the size of the sample window, and ε CV is a user-defined convergence threshold (a sensitivity analysis of ε CV is extensively reported in [45] and briefly summarized in Sec.8.5). To avoid biases, new samples are collected only if (i) the cache has received a non-null number of requests since the last sample, and (ii) its state has changed, i.e., at least a new content has been admitted in the cache since the last sample 2 .…”
Section: Steady-state Monitormentioning
confidence: 99%
See 1 more Smart Citation
“…In case of a full cache, the system evicts the content which was earliest stored and replaces it by the new content. For the distribution of requests and contents, studies have confirmed Zipfs law as an appropriate distribution model for access pattern to contents on the Internet such as videos hosted on YouTube [23] or peer-to-peer file sharing systems (Bit-Torrent, Gnutella) [24] [25]. According to Zipfs law, a small fraction of popular web objects attracts most user requests, which is favourable for the efficiency of small caches [25].…”
Section: Fig 5 Cache Hit Ratio Of Fuzzy Caching System Lru and Fifomentioning
confidence: 99%